Kinerja Pegawai Imbas dari Kualitas Kehidupan Kerja dan Peningkatan Profesionalisme yang Diterapkan pada Disdukcapil Kabupaten Bireuen - Win Konadi; Mahyu Danil; Umar Iskandar (Aceh Cooperative Care, 2025)
The research was conducted at the Population and Civil Registry Office (Disdukcapil) of Bireuen Regency, on the impact of quality of work life and work professionalism on improving employee performance. Using associative research with data collection through questionnaires and statistical analysis in processing data in the form of regression and correlation analysis tools. The results found (1) Quality of work life has a positive and significant impact on employee performance. (2) Work professionalism has a positive and significant impact on employee performance. (3) Simultaneously, quality of work life and work professionalism have a positive and significant impact on employee performance at the Bireuen Regency Disdukcapil Office by 53.3%.